Colonic atresia with modified Santulli procedure - Henggar Allest Pratama; Supangat (Elsevier, 2020)
Colonic atresia is one of the rarest congenital intestinal atresia. The incidence is estimated between 1:40,000 to 1:66,000 live births. The clinical manifestation of colonic atresia is abdominal distension in 24-48 hours after birth progressively, failure to pass meconium, and feculent vomiting as late manifestation. Colonic atresia need to receive surgical treatment as soon as possible. The surgical technique to treat colonic atresia could be different one each another based on patient condition and operator's experience. We describe a case of colonic atresia that was performed a modified Santulli procedure. As the result, patient could perform defecation from anus with minimal production of stoma and no post-operative complication. In conclusion, this technique has some advantages and could be one of surgical technique to treat colonic atresia.